Non-Targeted Metabolomics Analysis Unravels Changes in Non-Volatile Metabolites in Folium nelumbinis (Lotus Leaf) Induced by Aspergillus cristatus-Mediated Fermentation - Wei Dai; Yumei Tan; Shengling He; Luona Zhou; Xiyi Ren; Yonghui Huang; Li Song; Yongxiang Liu (Fermentation)
This study employed non-targeted metabolomics to investigate the impact of solid-state fermentation by Aspergillus cristatus on the major non-volatile metabolites in lotus leaves (Folium nelumbinis). Sensory evaluation and metabolomic analysis of the leaves before and after fermentation revealed that the fermentation process significantly enhanced the sensory quality of lotus leaf tea, resulting in a brighter infusion color, a mellow flavor profile, and a notable reduction in astringency. The fermentation also induced the production of several potentially bioactive metabolites, including chlorogenic acid and sphondin, and stimulated the expression of genes related to the phenylpropanoid pathway, thereby promoting the synthesis of chlorogenic acid. Additionally, the fermentation led to a marked decrease in the content of flavonoids, while the content of alkaloids remained relatively unchanged. This study provides a theoretical basis for the in-depth development and utilization of lotus leaves and offers a novel approach to applying microbial fermentation technology to medicinal and edible materials.